2015
DOI: 10.1093/mnras/stu2694
|View full text |Cite
|
Sign up to set email alerts
|

Early formation of massive, compact, spheroidal galaxies with classical profiles by violent disc instability or mergers

Abstract: We address the formation of massive stellar spheroids between redshifts z = 4 and 1 using a suite of AMR hydro-cosmological simulations. The spheroids form as bulges, and the spheroid mass growth is partly driven by violent disc instability (VDI) and partly by mergers. A kinematic decomposition to disc and spheroid yields that the mass fraction in the spheroid is between 50% and 90% and is roughly constant in time, consistent with a cosmological steady state of VDI discs that are continuously fed from the cosm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 110 publications
(155 reference statements)
10
100
1
Order By: Relevance
“…Cheung et al 2012;Fang et al 2013; and suggests that the immediate starforming progenitors of quiescent galaxies experience a phase of stronger core growth that increases their concentration with respect to galaxies growing along the M  Srelations. At high redshifts, this phase is consistent with the compaction evolutionary tracks predicted in hydrodynamical simulations (Ceverino et al 2015;Zolotov et al 2015;Tacchella et al 2016), which are typically associated with strongly dissipational (gas-rich) processes such as major mergers and interaction driven gravitational instabilities (Dekel et al 2009a;Ceverino et al 2010;. At lower redshifts, these gas-rich processes probably coexist with minor mergers and secular instabilities (e.g., bars and spiral arms; Kormendy & Kennicutt 2004).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Cheung et al 2012;Fang et al 2013; and suggests that the immediate starforming progenitors of quiescent galaxies experience a phase of stronger core growth that increases their concentration with respect to galaxies growing along the M  Srelations. At high redshifts, this phase is consistent with the compaction evolutionary tracks predicted in hydrodynamical simulations (Ceverino et al 2015;Zolotov et al 2015;Tacchella et al 2016), which are typically associated with strongly dissipational (gas-rich) processes such as major mergers and interaction driven gravitational instabilities (Dekel et al 2009a;Ceverino et al 2010;. At lower redshifts, these gas-rich processes probably coexist with minor mergers and secular instabilities (e.g., bars and spiral arms; Kormendy & Kennicutt 2004).…”
Section: Discussionsupporting
confidence: 81%
“…The blue and red lines show the best-fit e S and 1 S relations at z 1 and z 2 from Figure 2 (the z = 2 lines are higher). The model tracks are in excellent agreement with the observed distributions in e S and 1 S (see also Figure 12 of Ceverino et al 2015) and exhibit good agreement with the main evolutionary phases discussed in Section 4.1 (blue arrows), namely (1) a phase of relatively smooth structural growth that follows approximately the best-fit e S and 1 S relations from the data ( 0.6 a~, 0.9 b~) and (2) a phase of compaction, a period of steeper core growth ( 1.5 a~, 1.3 b~), usually triggered by a strongly dissipational event. The simulations exhibit a downsizing trend, such that the most massive galaxies evolve earlier and experience a stronger compaction event (open star) due to higher gas fraction at high z.…”
Section: Trends In Hydrodynamical Simulationssupporting
confidence: 78%
See 1 more Smart Citation
“…The models proposed by Tassis et al (2008) introduce a critical density threshold for the activation of star-formation, without requiring outflows to reduce the star formation efficiency and the metal content. Finally, the observed MZR can be explained assuming accretion of metal-poor gas along filaments from the cosmic web (cold-flows) (e.g., Dalcanton et al 2004;Ceverino et al 2015;Sánchez Almeida et al 2014b), for which also indirect evidences have been found in recent observations (Sánchez Almeida et al 2015).…”
Section: Introductionmentioning
confidence: 86%
“…In other words, does some physical process associated with stellar compactness predispose galaxies to quench? Alternatively, are the earliest galaxies to form and complete their evolution simply the densest because the universe was denser at early times (e.g., Lilly & Carollo 2016), or is itbecause of some highly dissipative gaseous process that could take place predominantly at high redshift (e.g., Dekel et al 2009;Johansson et al 2012;Dekel & Burkert 2014;Ceverino et al 2015;Zolotov et al 2015)?…”
Section: Introductionmentioning
confidence: 99%